In vitro antimicrobial activity of honokiol against Staphylococcus aureus in biofilm mode. Issue 12 (1st December 2016) - Li, Wen-Li; Zhao, Xing-Chen; Zhao, Zi-Wen; Huang, Yan-Jun; Zhu, Xuan-Zhi; Meng, Ri-Zeng; Shi, Ce; Yu, Lu; Guo, Na
Abstract: Staphylococcus aureus ( S. aureus ) can attach to food, host tissues and the surfaces of medical implants and form a biofilm, which makes it difficult to eliminate. The purpose of this study was to evaluate the effect of honokiol on biofilm-grown S. aureus . In this report, honokiol showed effective antibacterial activity against S. aureus in biofilms. S. aureus isolates are capable of producing distinct types of biofilms mediated by polysaccharide intercellular adhesion (PIA) or extracellular DNA (eDNA). The biofilms' susceptibility to honokiol was evaluated using confocal laser scanning microscopy (CLSM) analysis. The transcript levels of the biofilm-related genes, the expression of PIA, and the amount of eDNA of biofilm-grown S. aureus exposed to honokiol were also investigated. The results of this study show that honokiol can detach existing biofilms, kill bacteria in biofilms, and simultaneously inhibit the transcript levels of sarA, cidA and icaA, eDNA release, and the expression of PIA.